Cytokine therapies in HIV-1 infection: present and future. Issue 1 (1st June 2003) - Pett, Sarah L; Kelleher, Anthony D
Since the introduction of highly active antiretroviral therapy (HAART), HIV-related deaths have declined dramatically in the developed world. However, HAART is neither able to eradicate the virus nor are its immunomodulatory effects sufficient to effect complete control of the virus. In addition, the long-term use of HAART is complicated by drug-related toxicities and compliance issues, both of which impact upon the development of viral resistance. The failure of structured treatment interruption strategies in those with chronic HIV-infection combined with the above limitations, has prompted renewed interest in immunotherapy. Cytokines and therapeutic vaccination have been proposed as HAART-adjunctive and HAART-sparing treatments in HIV-infection, and the current and future role of cytokine therapy in this disease will be the subject of this review.